Mesoporous electro-adsorption defluorination positive electrode material rich in defects after vulcanization reconstruction

By hydrothermal reconstruction of nanorods encapsulated bismuth, defect-rich mesoporous carbonaceous electrode positive electrode material was developed, which solved the problem of insufficient research on bismuth atom/cluster diffusion and reconstruction during the vulcanization process in the prior art. It achieves efficient fluorine removal performance and stable emission effects.

CN119409294AInactive Publication Date: 2025-02-11NANKAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411875453.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art lacks research on bismuth atom/cluster diffusion and reconstruction during the vulcanization process, especially how defects on mesoporous materials obtained by partial vulcanization affect the ion removal behavior under the influence of potential difference, lack of detailed characterization and theoretical explanation .

Method used

By hydrothermal reconstruction by encapsulating bismuth nanorods, a mesoporous carbon electrode positive electrode active material was developed, and the carbon skeleton was modified using thioacetamide, introducing a large number of defects and pore structures to enhance the fluorine removal performance of the material.

Benefits of technology

It has achieved excellent desorption capacity and capacity retention ability in the case of many competitive ions and acid-base imbalances, and the effluent can be stable below the emission standards, which is suitable for sewage treatment and environmental restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409294A_ABST
    Figure CN119409294A_ABST
Patent Text Reader

Abstract

The invention discloses a mesoporous electro-adsorption defluorination positive electrode material rich in defects after vulcanization reconstruction, which is prepared by the following steps: preparing a bismuth-doped and defect-rich mesoporous carbon material, including ultrasonic vibration stirring, hydrothermal treatment in an organic environment, nitrogen atmosphere annealing and secondary hydrothermal treatment in which sulfur participates; the electro-adsorption positive electrode material belongs to a sulfur-modified bismuth-containing mesoporous synergistic platform embedded in a carbon shell, and has the defects of a nano frame with strong pore accessibility and high density; the synergistic process comprises double-electric-layer capacitive adsorption and reversible oxidation-reduction conversion. The nanometer configuration reduces the dependence on slow diffusion, reduces the activation energy barrier, and shows high redox activity. The electrode prepared by the method has a unique mesoporous framework, a large number of defluorination sites are obtained on the surface of the electrode, a rapid ion storage behavior mainly based on a capacitance control process is realized on a solid-liquid interface, fluorine-containing substances in water can be effectively separated in an electro-adsorption system, and the method is a pollution control process with a clear mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mesoporous materials, and in particular relates to a defect-rich mesoporous electro-absorption fluorine removal positive electrode material after sulfurization reconstruction. Background Art

[0002] Electrodefluorination is a very promising technology to achieve stringent emission standards, which largely depends on the development of electrode materials. The kinetic behavior of fluoride anion electrosorption is deeply affected by the microstructure of the prepared composite material.

[0003] The proper reconstruction of the microstructure of carbon materials and the migration and rearrangement of bismuth atoms / clusters can expose more active sites and optimize the coordination environment, which is conducive to reducing the activation energy barrier and accelerating the binding with active sites. At the same time, the defects of unsaturated coordination sites and exposed dangling bonds can enhance the interaction with ion adsorption by inducing lattice distortion and changing the hybrid orbital type of C atoms, which is an effective way to enhance the microscopic inter-ionic force.

[0004] Although Bi2S3 obtained by converting bismuth-containing precursors (such as bismuth or bismuth oxides) has become a promising electrode material due to its high capacity, the diffusion and reconstruction of bismuth atoms / clusters during the sulfurization process and their impact on the microstructure have not been extensively studied. In particular, how the defects on the mesoporous materials obtained by partial sulfurization affect the ion removal behavior under the action of potential difference compared with pure Bi2S3, in short, still lacks detailed characterization and theoretical explanation. Summary of the invention

[0005] The purpose of the present invention is to break through the theoretical blind spot and improve the effect of the prior art. To this end, the present invention provides a positive electrode for an upward flow electrosorption system, wherein the positive electrode material is made of a mixture of three substances, including an active material proposed by the present invention. The system has excellent desorption capacity under the drive of an appropriate external voltage, has good capacity retention ability under the conditions of more competitive ions and acid-base imbalance, and at the same time, the effluent can be stably lower than the emission standard under certain conditions, and can be used as a sample pretreatment medium in the fields of sewage treatment and environmental remediation.

[0006] The present invention also provides a method for preparing the positive electrode of the electric adsorption system.

[0007] The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction of the present application is prepared by mixing a binder PTFE, conductive carbon black and an active material, which are added to a beaker in a mass ratio of 1:1:7 to 9. After mixing, ethanol (or deionized water or methanol) is added and ultrasonic treatment is performed. After dispersion and mixing, drying is performed to obtain a defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction.

[0008] The active material surface has a large number of mesopores and micropores, and exhibits a large number of defects at the micro-nanostructural level. The electrode has the following structural characteristics: by introducing coordinated sulfur (S), the microstructure of the defluorination unit is precisely regulated to obtain a defect-rich porous framework, making it a synergistic platform for efficient defluorination, achieving a strong interaction between the electrode and fluoride ions, and exhibiting capacitance-controlled electrochemical characteristics during rapid ion storage.

[0009] The method for preparing the active material is divided into two steps:

[0010] a) Preparation of carbon framework: First, the precursor Bi-MOF (CAU-17) is synthesized, and bismuth nitrate pentahydrate and trimesic acid are dissolved in 50-70 ml of methanol or deionized water, pure water, or ultrapure water solution at a mass ratio of 1:4.5-5.5. The resulting solution is kept at 115-125°C for 20-30 hours, centrifuged and washed to obtain a white solid, which is dried in an oven at 60°C overnight to obtain the post-Bi-MOF. The precursor is pyrolyzed in a tubular furnace under a nitrogen atmosphere at a heating rate of 5°C / min, heated to 795-805°C, and then kept at this temperature for 4 hours. The black solid particles are washed to facilitate the next step of treatment, which is called a carbon framework encapsulating bismuth;

[0011] b) Preparation of active material: The carbon framework and thioacetamide are hydrothermally treated in deionized water (or methanol, pure water, ultrapure water); in a polytetrafluoroethylene container with a Teflon steel liner, thioacetamide is dissolved in 50-100 mL of deionized water (or methanol, pure water, ultrapure water), and after adding the carbon framework, the mixture is maintained at 120-180° C. for 4-12 hours; and the active material is obtained.

[0012] In the active material, the sulfur element in thioacetamide acts as a heteroatom to induce bismuth elements and carbon skeletons to reconstruct the nanostructure. The bismuth element undergoes atomic / cluster diffusion and partially combines with sulfur atoms to achieve reconstruction. The carbon skeleton also exhibits a large number of intrinsic defects after sulfurization.

[0013] In the method for preparing the active material, the solvent in step a) is preferably methanol.

[0014] In the method for preparing the active material, the mass ratio of the carbon framework to thioacetamide in step b) is preferably 4.8-5.2:1.

[0015] In the method for preparing the active material, the reaction temperature in step b) is preferably 120°C to 130°C.

[0016] In the method for preparing the active material, the reaction time in step b) is preferably 4 h to 5 h.

[0017] In the method for preparing the active material, the solvent in step b) is preferably deionized water.

[0018] The positive electrode material is used for environmental remediation, specifically for the electrical adsorption and capture of excess fluoride ions in water environments to remove harmful fluoride ions.

[0019] The present invention develops a mesoporous carbon electrode positive active material by hydrothermal reconstruction of bismuth-encapsulated nanorods to improve the fluorine removal performance of the upflow electrosorption system. The synergistic combination of surface redox and double-layer capacitance realizes the rapid electrosorption of fluoride, which has guiding significance for designing efficient carbon electrochemical removal anodes.

[0020] The present invention provides a method for creating defects on a carbon skeleton, using sulfur to modify a mesoporous carbon platform. Through this method, the platform not only has a large number of mesopores and micropores, but also exhibits a large number of defects at the micro-nanostructural level.

[0021] The cathode active material of the present invention is denoted as BiMCS-P, where BiM refers to the Bi-MOF precursor (CAU-17); C refers to the annealing carbonization of Bi-MOF under a nitrogen atmosphere; S refers to the hydrothermal treatment with the participation of thioacetamide, and -P represents the degree of sulfidation, which is defined as partial sulfidation, that is, the active metal is not completely converted into a sulfur compound. For this incomplete sulfidation process, due to the incomplete conversion, the disordered evolution leads to a disordered structure, and the "partiality" of the conversion is conducive to the material to reconstruct more active sites and introduce defects into the composite material.

[0022] Before hydrothermal treatment, the mixed solution needs to be subjected to ultrasonic vibration and stirring to ensure full dissolution and uniform contact, which is conducive to the introduction of sulfur atoms.

[0023] After the reaction is completed, the reaction product is washed with deionized water to remove heteroatoms that are not introduced into the system framework.

[0024] The final product was obtained by drying at 60°C overnight.

[0025] The active material in the positive electrode of the electric adsorption system of the present invention has at least the following beneficial effects: it has defluorination sites for EDL double-layer capacitance adsorption and Faraday reversible transformation, and as an active material with high redox activity and high surface charge density, it can be used in the fields of environmental remediation and sewage treatment by combining with the electric adsorption system.

[0026] The active material in the positive electrode of the electric adsorption system of the present invention is a nanorod encapsulating bismuth as a precursor, and the porosity of the conductive framework is optimized by appropriate doping with thioacetamide. The topological defects and intrinsic defects enhance the activity of the surface redox defluorination sites, releasing the super affinity of the electrode material for the target fluorine pollutant at the solid-liquid interface. The synergistic combination of surface redox and double-layer capacitance realizes the rapid electric adsorption of fluoride, showing excellent performance in pollutant emission compliance.

[0027] The active material in the positive electrode of the electric adsorption system of the present invention is characterized by scanning electron microscopy and transmission electron microscopy, X-ray diffraction, Raman spectroscopy, N2 adsorption and desorption test, X-ray photoelectron spectroscopy and infrared spectroscopy, and tested by a series of fluorine removal experiments. The results show that the active material has good removal ability, good stability, a rod-like structure within nano-confinement, good application prospects, and low preparation cost.

[0028] The active material in the positive electrode of the electric adsorption system of the present invention also shows practicality in weakly acidic solutions and maintains the regenerative electric absorption capacity in continuous cycles.

[0029] The beneficial effects of the active material in the positive electrode of the electrosorption system of the present invention can be further summarized as follows:

[0030] The active material in the positive electrode of the electric adsorption system of the present invention, as an electroactive material, accurately adjusts the reaction activity of the surface redox reaction, improves the accessibility of the surface double-layer capacitance site, optimizes the kinetic characteristics of the electric adsorption behavior, has excellent adsorption capacity, rapid kinetic behavior, simple preparation, and has the potential for large-scale use.

[0031] The active material in the positive electrode of the electric adsorption system of the present invention has a rough porous structure on the surface, has obvious lattice stripes, and has a mixed structure of mesopores and micropores. The metal components are successfully embedded, have multi-layer force, and the force is strong, and have good fluorine removal performance even at low concentrations.

[0032] The active material in the positive electrode of the electric adsorption system of the present invention, as an effective electric adsorption electrode, provides a technical basis for the preparation and application of a defect-rich composite carbon framework based on thioacetamide or the like as an inducer.

[0033] According to some embodiments of the present invention, in the positive electrode active material, defect engineering induces lattice distortion and changes the hybrid orbital type of C atoms, resulting in the generation of coordination unsaturated sites and exposed dangling bonds, thereby achieving a higher fluoride ion adsorption capacity. The rich defect and pore skeleton structure constructed in the electrode prepared by the present invention is shown in the figure below: Fig.11 .

[0034] According to some embodiments of the present invention, in the positive electrode active material, bismuth atoms / clusters and coordinated sulfur atoms undergo diffusion and recombination during the crystal topological transformation, and the formed topological defects serve to reduce the reaction activation energy, ultimately achieving a higher fluoride ion adsorption capacity.

[0035] The present invention provides application of the positive electrode material in separating harmful substances in the environment.

[0036] The present invention develops a mesoporous carbon electrode positive active material by hydrothermal reconstruction of bismuth-encapsulated nanorods to improve the fluorine removal performance of the upflow electrosorption system. The synergistic combination of surface redox and double-layer capacitance realizes the rapid electrosorption of fluoride, which has guiding significance for designing efficient carbon electrochemical removal anodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 N2 adsorption / desorption isotherm curve of BiMCS-P, an electrode material prepared in an embodiment of the present invention;

[0038] Figure 2 The pore size distribution of the electrode material BiMCS-P prepared in the embodiment of the present invention;

[0039] Figure 3 This is an infrared characterization image of the electrode material BiMCS-P prepared in an embodiment of the present invention;

[0040] Figure 4 This is a Raman characterization image of the electrode material BiMCS-P prepared in an embodiment of the present invention;

[0041] Figure 5 This is an X-ray diffraction characterization diagram of the electrode material BiMCS-P prepared in an embodiment of the present invention;

[0042] Figure 6 This is an X-ray photoelectron spectroscopy characterization diagram of the electrode material BiMCS-P prepared in an embodiment of the present invention;

[0043] Figure 7 The voltammetric cycle curve of the electrode material BiMCS-P prepared in the embodiment of the present invention;

[0044] Figure 8 This is a graph showing the adsorption capacity of the electrode material BiMCS-P prepared in an embodiment of the present invention for fluoride-containing wastewater;

[0045] Fig. 9 The adsorption of low concentration fluoride ions by the electrode material BiMCS-P prepared in the embodiment of the present invention;

[0046] Fig.10 This is a perspective electron microscope image of the electrode material BiMCS-P prepared in an embodiment of the present invention;

[0047] Fig.11 Schematic diagram of the rich defects and pore skeleton structure constructed in the electrode prepared by the present invention. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0049] Example 1

[0050] This embodiment specifically prepares a positive electrode active material, which includes a sulfur-modified mesoporous carbon platform with bismuth embedded therein, wherein the platform has a large number of mesopores and micropores and exhibits a large number of defects at the micro-nanostructural level.

[0051] The positive electrode active material prepared in this example is denoted as BiMCS-P, wherein BiM refers to the Bi-MOF precursor (CAU-17), C refers to annealing carbonization under nitrogen atmosphere, S refers to hydrothermal vulcanization under the action of thioacetamide, and P indicates that the degree of vulcanization is appropriate under temperature control, which is defined as partial vulcanization.

[0052] The preparation method is:

[0053] Preparation of carbonaceous precursors, Bi(NO3)3·5H2O bismuth nitrate pentahydrate and trimesic acid were 150mg and 750mg respectively, and dissolved in 60ml methanol by ultrasonic oscillation for 30 minutes, stirring for 3h, and then the mixed solution was transferred to a 100mL stainless steel autoclave with Teflon memory and sealed. Heated at 180℃ for 24h, then centrifuged to collect the white product, and after drying, heated to 800℃ at a heating rate of 5℃ / min in a nitrogen atmosphere, and maintained for 4h. The obtained black product was washed and dried in an oven overnight.

[0054] Preparation of BiMCS-P active electrode material: 125 mg of carbonaceous precursor and 625 mg of thioacetamide were mixed in 37.5 mL of deionized water, and the mixed solution was transferred to a 100 mL stainless steel high-pressure reactor with Teflon memory and sealed, and heated at 120°C for 4 h. The black insoluble matter was washed and collected, and dried in an oven overnight to obtain BiMCS-P.

[0055] Preparation of the positive electrode of the electrosorption system: 48 mg of active material BiMCS-P, 6 mg of PTFE (diluted 20 times with ethanol for easy transfer) and 6 mg of conductive carbon black are added to a 50 ml beaker, and ethanol is added until the bottom of the beaker is just filled. The mixed liquid is subjected to ultrasonic vibration for 30 minutes, and the mixture is transferred to an agate mortar and ground until the ethanol is completely evaporated. A few drops of ethanol solution are added and grinding is continued to obtain a black colloidal mixture, which is the positive electrode material for coating on the electrode sheet.

[0056] The specific surface area and porosity were studied using N2 adsorption-desorption isotherms, such as Figure 1 and Figure 2 As shown in Figure 2, the specific surface area of ​​the BiMCS-P composite material is approximately 16.64 m 2 g -1 , the pore diameters are mostly between 3-11nm.

[0057] Fourier transform infrared spectroscopy was used to investigate Figure 3 All prepared BiMCS-P exhibited strong hydroxyl stretching. After sulfurization, the C=O peak, the asymmetric and symmetric vibration peaks of the carboxyl group, and the Bi-O band disappeared, and the Bi-S band appeared, which confirmed the crystallographic transformation.

[0058] Raman spectroscopy was used to analyze the structural features and electronic properties of the reconstructed BiMCS-P. Figure 4 , showing two obvious signals, which correspond to the sp3 defect or disorder characteristics of graphene species and the sp 2 In-plane vibration, about 270cm -1 The signal at corresponds to Bi 3+ characteristic vibration.

[0059] X-ray diffraction confirmed that the prepared electrode material had good crystallinity and purity, such as Figure 5 Characteristic reflections appeared at 24.9°, 28.7°, and 31.8°, corresponding to Bi2S3 (JCPDS 75-1306), which may be due to the conversion of Bi to Bi2S3 caused by ligand exchange and lattice matching.

[0060] The chemical composition and electronic state of the composite BiMCS-P were investigated by X-ray photoelectron spectroscopy. Figure 6 As shown, the spectral investigation shows that BiMCS-P is mainly composed of C, O, S and Bi elements, which is consistent with the above results.

[0061] At 0.5 mol L -1 The voltammetric cycling test of BiMCS-P was carried out in NaF solution using a three-electrode system. Figure 7As shown in Figure 3, the ring area expands with the increase of scan rate. BiMCS-P maintains a clear redox peak, which corresponds to the highly reversible surface redox reaction.

[0062] BiMCS-P was used as the active material to prepare the electrosorption positive electrode, which was introduced into the upward flow electrosorption system. Under the condition of 100 mg / L fluoride ion concentration, the adsorption capacity of the active electrode for fluoride ions was evaluated by equilibrium adsorption experiments. Figure 8 As shown, the results indicate that its adsorption capacity is as high as 60.23 mg / g, which is inseparable from the unique mesoporous structure and abundant defluorination sites on the surface.

[0063] BiMCS-P was used as an active material to prepare an electrosorption cathode, which was introduced into an upward flow electrosorption system. The removal performance of fluoride ions was studied under low fluoride ion concentrations of 5 and 2.5 mg / L. The results showed that ( Fig. 9 ), after 3 hours, the effluent is lower than the limit of fluoride ion concentration in the discharge standard of the South Four Lakes Basin, and has the potential for further expansion of utilization.

[0064] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction, characterized in that: The electrode is prepared by mixing a binder PTFE, conductive carbon black and an active material, which are added into a beaker at a mass ratio of 1:1:7-9. After mixing, ethanol or deionized water or methanol is added and ultrasonic treatment is performed. After dispersion and mixing, drying is performed to obtain a defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction.

2. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 1, characterized in that: The method for preparing the active material is divided into two steps: a) Preparation of carbon framework: First, the precursor Bi-MOF (CAU-17) is synthesized, and bismuth nitrate pentahydrate and trimesic acid are dissolved in 50-70 ml of methanol or deionized water, pure water, or ultrapure water solution at a mass ratio of 1:4.5-5.

5. The resulting solution is kept at 115-125°C for 20-30 hours, centrifuged and washed to obtain a white solid, which is dried in an oven at 60°C overnight to obtain the post-Bi-MOF. The precursor is pyrolyzed in a tubular furnace under a nitrogen atmosphere at a heating rate of 5°C / min, heated to 795-805°C, and then kept at this temperature for 4 hours. The black solid particles are washed to facilitate the next step of treatment, which is called a carbon framework encapsulating bismuth; b) Preparation of active material: hydrothermally treat the carbon framework and thioacetamide in deionized water or methanol, pure water, or ultrapure water; dissolve thioacetamide in 50-100 mL of deionized water or methanol, pure water, or ultrapure water in a polytetrafluoroethylene container with a Teflon steel liner, add the carbon framework, and maintain at 120-180° C. for 4-12 hours; obtain the active material.

3. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 2, characterized in that: In the method for preparing the active material, the solvent in step a) is methanol.

4. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 2, characterized in that: In the method for preparing the active material, the mass ratio of the carbon framework to thioacetamide in step b) is 4.8-5.2:

1.

5. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 2, characterized in that: In the method for preparing the active material, the reaction temperature in step b) is 120°C to 130°C.

6. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 2, characterized in that: In the method for preparing the active material, the reaction time in step b) is 4h to 5h.

7. The defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 2, characterized in that: In the method for preparing the active material, the solvent in step b) is deionized water.

8. A method for applying the defect-rich mesoporous electrosorption defluorination cathode material after sulfurization reconstruction according to claim 1, characterized in that: The positive electrode material is used for environmental remediation, specifically for the electrical adsorption and capture of excess fluoride ions in water environments to remove harmful fluoride ions.

Citation Information

Patent Citations

  • Lithium-sulfur battery composite positive electrode material and preparation method thereof

    CN104538608A

  • Preparation method of cerium-aluminum organic framework modified biomass carbon composite material for fuel cell negative electrode

    CN115939422A

  • Capacitive deionization electrode for treating low-concentration fluorine ion wastewater as well as preparation and application of capacitive deionization electrode

    CN118745028A

  • Preparation method and application of porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects

    CN118825244A

  • Method for changing fluorine ion battery electrode material into fluorine ion electro-adsorption electrode and application of fluorine ion battery electrode material

    CN118929850A